Reduction of the in vivo allergenicity of Der p 2, the major house-dust mite allergen, by genetic engineering - Chen, K. W.; Fuchs, G.; Sonneck, K.; Gieras, A.; Swoboda, I.; Douladiris, N.; Linhart, B.; Jankovic, M.; Pavkov, T.; Keller, W.; Papadopoulos, N. G.; Valent, P.; et al. (Mol Immunol, 2008)
The major allergen of the house-dust mite Dermatophagoides pteronyssinus, Der p 2, is recognized by approximately 90% of mite-allergic patients. We have produced two recombinant fragments of Der p 2 comprising aa 1-53 and aa 54-129 and a hybrid molecule (aa 54-129+1-53), combining the two fragments in inverse order, by genetic engineering. The recombinant Der p 2 derivatives were expressed in E. coli and purified to homogeneity. rDer p 2 derivatives (fragments and hybrid) showed a considerably reduced beta sheet structure and IgE reactivity compared to the Der p 2 wild-type allergen. The allergenic activity of the Der p 2 derivatives was reduced more than tenfold as evaluated in vitro in basophil activation assays and in vivo by skin prick testing of mite-allergic patients. Immunization of mice and rabbits with rDer p 2 derivatives induced Der p 2-specific IgG antibodies, which inhibited the binding of allergic patients' IgE to Der p 2. Immunization of mice with rDer p 2 derivatives induced less allergenic IgE responses than immunization with rDer p 2. Thus the rDer p 2 derivatives exhibited less in vivo allergenic activity and allergenicity than the Der p 2 allergen but preserved immunogenicity and may hence represent candidates for specific immunotherapy of house-dust mite allergy.
Keywords: Allergens Animals Antigens; Dermatophagoides Arthropod Proteins Basophils Cloning; Immediate Immunoglobulin E Immunoglobulin G Mice Rabbits Recombinant Fusion Proteins Skin Tests beta-N-Acetylhexosaminidases; Molecular Dermatophagoides pteronyssinus Genetic Engineering Humans Hypersensitivity